The impact of urbanization on the psychophysiological health of residents of megacities in the conditions of the COVID-19 pandemic - Luchina, Victoria N.; Sivukha, Valeria V. (Journal of the Belarusian State University. Ecology, 2022)
There are many studies on the COVID-19 pandemic in Europe, Asia and America. These studies prove that the main factors negatively affecting the mental and somatic health of people include social distancing. Most countries of the world have used the practice of quarantine in order to reduce the burden on the healthcare system. The decrease in social contacts due to forced self-isolation has caused some psychological problems, such as apathy, stress, fear, loneliness, which also inevitably arise among residents of modern megacities, as factors of the influence of urbanization on the psychophysiological state of people’s health. Also, the issue of professional burnout is relevant for medical personnel working in the “red zone”, exposed to the threat of infection and extreme stress.